Dampak Promosi Media Digital terhadap Peningkatan Penjualan Jengkol Sehat (Jukolat) - Heryyanoor, Heryyanoor; Pefbrianti, Diana; Kholdani, Al Fath Riza; Febriana, Annisa; Syafariansyah, Hari (Universitas Batanghari Jambi, 2025)
This study aims to analyze the impact of digital media promotion on increasing sales of healthy jengkol (jukolat) in a group of jengkol sellers. This type of research is quasi-experimental with a pre-test and post-test approach. The population and sample were 18 respondents of healthy jengkol sellers (Jukolat). The independent variable is the use of digital media promotion, while the dependent variable is the increase in sales before and after using digital media promotion. The instrument in the study was a questionnaire related to the parameters of each variable using a Likert scale with a score of 1-5 then analyzed using the Wilcoxon test. The results of the study prove that the use of digital media promotion has an effect on increasing sales of healthy jengkol (jukolat), where the better the seller utilizes digital promotional media, the more it will increase sales and income.